2008
DOI: 10.1002/eji.200838668
|View full text |Cite
|
Sign up to set email alerts
|

TCR‐β chains derived from peripheral γδ T cells can take part in αβ T‐cell development

Abstract: Between 10 and 20% of the peripheral cd T cells express cytoplasmic TCR-b proteins, but whether such TCR-b chains can partake in ab T-cell development has never been systematically investigated. Therefore, we reconstituted the T-cell compartment of CD3e-deficient mice with Pax5-TCR-b deficient proB cells expressing, via a retroviral vector, TCR-b chains from either peripheral cd or ab T cells. Recipient thymi reconstituted with proB cells containing empty vector were small (o15 Â 10 6 cells), contained few cd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…2 D). Lack of pT expression in  precursor cells can thus be formally excluded as an explanation for the presence of functional TCR chains in a significant percentage of  T cells (Bosco et al, 2008). pT iCre expression is confined to T progenitors lacking B cell, NK cell, and myeloid lineage potential If pT was expressed in a T lineage precursor population with physiologically relevant CLP activity, as suggested previously intermediate progenitors (CIPs) to be described below.…”
Section: Generation Of Pt Icre Knockin Mice For Lineage-tracing Expementioning
confidence: 79%
“…2 D). Lack of pT expression in  precursor cells can thus be formally excluded as an explanation for the presence of functional TCR chains in a significant percentage of  T cells (Bosco et al, 2008). pT iCre expression is confined to T progenitors lacking B cell, NK cell, and myeloid lineage potential If pT was expressed in a T lineage precursor population with physiologically relevant CLP activity, as suggested previously intermediate progenitors (CIPs) to be described below.…”
Section: Generation Of Pt Icre Knockin Mice For Lineage-tracing Expementioning
confidence: 79%
“…However, aberrant expression of TCR chains has been demonstrated among αβ and γδ T cell populations ( Bowen et al, 2014 ; Hochstenbach and Brenner, 1989 ; Ishida et al, 1990 ). For example, in-frame TCRδ rearrangements have been identified in αβ T cells ( Livak et al, 1995 ), and functional TCRβ rearrangements have been detected in γδ T cells ( Bosco et al, 2008 ). The latter may even confer a proliferative advantage and selectively amplify certain subsets of murine TCRβ + γδ thymocytes ( Wilson and MacDonald, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to exclude these observations as artifacts of ex vivo culture systems, we compared our findings with established literature data, and in order to identify its physiological relevance, we aimed to show analogs of this new developmental pathway in vivo . Several groups of researchers have shown that around 10–20% of all peripheral γδ T cells transcribe and express in-frame TCR-β rearrangements ( 63 – 65 ) that can guide αβT-cell development, resulting in fully functional, mature T cells ( 66 ). Consistent with these findings, CD4 + Vδ1 + clones transcribed in-frame TCR-β chain rearrangements, showed cytoplasmic protein expression of TCR-β chains, and expressed the TCR-β chain on their cell surface as they bound BMA031.…”
Section: Discussionmentioning
confidence: 99%